Strategies and Business Models of Sharing Economy: MSMEs Digital Creativity - Rimawati, Yuni; Sula, Atik Emilia (Jurnal Ilmiah Akuntansi dan Bisnis, 2020)
This study aims to explore the business strategy of Pesan Antar and present its business model by referring to the economic sharing model between Micro, Small and Medium Enterprises (MSMEs).  The analysis of this study uses the ethnometodology method. The findings of this study are Pesan Antar has done a branding strategy before business activities begin. The strategy to maintain the loyalty of the courier, Pesan Antar applies a profit sharing and bonus mechanism, also implementing family culture to run business. Strategy to maintain business growth, Pesan Antar introducing other MSME products (though not yet a partner) no "fees" become a partner. To maintain customer loyalty, Pesan Antar strategy are “the rate” charged to customers is per region and order system using social media (not an application). Pesan Antar match with Type I economic models sharing among MSMEs Choi et al. (2014) . Keywords:  Business strategy, economic sharing model, MSMEs, digital creativity